2015
DOI: 10.1039/c5cp03704b
|View full text |Cite
|
Sign up to set email alerts
|

H2O–CH4and H2S–CH4complexes: a direct comparison through molecular beam experiments and ab initio calculations

Abstract: Electron density redistribution upon the formation of the water–methane complex arises from polarisation and charge transfer effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…As previously, ,,,,, in the present investigation each interaction center on the polyatomic molecules has been localized for C–H on the middle point of the bond, and for C–F and C–Cl, respectively, at about 60% and 80% of the bond length toward the halogen atom. , …”
Section: Atom-bond Pairwise Additive Representation Of the Pessupporting
confidence: 66%
“…As previously, ,,,,, in the present investigation each interaction center on the polyatomic molecules has been localized for C–H on the middle point of the bond, and for C–F and C–Cl, respectively, at about 60% and 80% of the bond length toward the halogen atom. , …”
Section: Atom-bond Pairwise Additive Representation Of the Pessupporting
confidence: 66%
“…Although experimental data [58,59] Later this conclusion was confirmed in a series of ab initio studies of the methanewater complex [66][67][68][69][70][71][72][73]. A theoretical investigation [74] of the adsorption of water on the methyl-terminated Si (111) surface and a recent study [75] of the n-alkanes...HX (X = F, OH) complexes also showed that XH...C interactions are stronger than CH...X hydrogen bonds.…”
Section: Introductionmentioning
confidence: 78%
“…This conclusion is supported by the work of Szczȩśniak et al [65], where noted that "the binding in CH 4 -H 2 O is chiefly due to the dispersion energy which sets the general trend for the anisotropy of the surface". According to the analysis of decomposition of the binding energy in the methanewater complex on components, the contribution of the dispersion energy may exceed 50% of the total stabilizing energy [72]. The dominant contribution of the dispersion energy, which is usual characteristic of van der Waals complexes, is also believed to be the feature of nonconventional hydrogen bonds [108].…”
Section: Geometry and Binding Energymentioning
confidence: 98%
“…They have been further accurately reproduced by an analytic potential formulation, tuned by few well‐defined physical parameters, the main ideas of which can be easily extended to more complex systems and can thus provide some basic ingredients of a comprehensive potential model for weak interactions. Future detailed comparison with established energy decompositions analysis could further benefit this endeavor. The model, which may easily be made to include also the dependence on the X 2 intramolecular distance, can be instrumental in formulating force fields suitable for molecular dynamics simulations of fundamental phenomena such as energy transfer processes…”
Section: Figurementioning
confidence: 99%
“…In conclusion, we have shown here,b yathoroughly integrated experimental and theoretical approach, the emergence of the halogen bond in the series of noble-gas-Cl 2 adducts.T he stereoselectivity of the interaction, as well as the CT that accompanies it, which only takes place in the collinear configuration when Cl 2 is in its ground state,h ave clearly been demonstrated. They have been further accurately reproduced by an analytic potential formulation, tuned by few well-defined physical parameters,the main ideas of which can be easily extended to more complex systems and can thus provide some basic ingredients of acomprehensive potential model for weak interactions.Future detailed comparison with established energy decompositions analysis [13b, 16,18] could further benefit this endeavor.T he model, which may easily be made to include also the dependence on the X 2 intramolecular distance,c an be instrumental in formulating force fields suitable for molecular dynamics simulations of fundamental phenomena such as energy transfer processes. [3]…”
Section: Angewandte Chemiementioning
confidence: 99%